Rainwater chemical composition and annual atmosphere depositon in Sorocaba (SP) - Conceição, Fabiano Tomazini da [UNESP]; Antunes, Maria Lúcia Pereira [UNESP]; Angelucci, Vivian Andréa [UNESP]; Moruzzi, Rodrigo Braga [UNESP]; Navarro, Guillermo Rafael Beltrano [UNESP] (My University, 2013)
This work evaluated the rainwater chemical composition and the annual atmospheric deposition in Sorocaba, (Sao Paulo State), Brazil. One sampling ˜ point was chosen and forty samples were collected between January and December 2006. The analyses were performed for pH, electrical conductivity, sodium, calcium, potassium, magnesium, sulphate, nitrate, phosphate, alkalinity and chloride. The rainwater pH varied from 5.20 to 6.40, being Ca2+ the main ion responsible for controlling the rainwater pH. The ionic concentration decreases in the following order: Ca2+>Na+> K+>Mg2+ for cations and SO2− 4 >HCO− 3 >NO− 3 >Cl−>PO3− 4 for anions. The annual atmospheric deposition appears to be controlled by the following sources: mining activities and cement factories (Ca2+ and HCO− 3 ), agricultural activities (K+, NO− 3 and PO3− 4 ), soil dust (Na+, Mg2+ and HCO− 3 ) and fossil fuel burning (SO2− 4 )

Este trabalho avaliou a composição química das águas pluviais e a deposiçãoo atmosférica anual na cidade de Sorocaba (SP). Um ponto de amostragem foi escolhido e quarenta amostras foram coletadas entre janeiro e dezembro de 2006. As amostras foram caracterizadas em relação ao pH, condutividade elétrica, sódio, cálcio, potássio, magnésio, sulfato, nitrato, fosfato, alcalinidade e cloreto. O pH das ´ aguas de chuva variou entre 5,20 e 6,40, sendo o Ca 2+ o principal íon responsavel pelo controle do pH das águas de chuva. A concentração iônica diminui na seguinte ordem: Ca 2+>Na+>K+>Mg2+ para os cations e SO2− 4 >HCO− 3 >NO− 3 >Cl−>PO3− 4 para os anions. A deposição atmosférica anual parece ser controlada pelas seguintes fontes: minerações e fábricas de cimeanto (Ca2+ e HCO− 3 ), atividades agrícolas (K+, NO− 3 e PO3− 4 ), poeira de solo (Na+, Mg2+ e HCO− 3 ) e queima de combustíveis fosseis (SO ´ 2− 4 ).
Keywords: Sorocaba; Rainwater composition; Air pollution; Sorocaba; Composição da água de chuva; Poluição atmosférica